2018
DOI: 10.1155/2018/2894247
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Exercise Protects against Cellular Stresses in Aged Mice

Abstract: The current study examined the effect of aging and long-term wheel-running on the expression of heat shock protein (HSP), redox regulation, and endoplasmic reticulum (ER) stress markers in tibialis anterior (T.A.) and soleus muscle of mice. Male mice were divided into young (Y, 3-month-old), old-sedentary (OS, 24-month-old), and old-exercise (OE, 24-month-old) groups. The OE group started voluntary wheel-running at 3 months and continued until 24 months of age. Aging was associated with a higher thioredoxin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…These data indicate an increase in ER stress levels in senile skeletal muscle. Studies on the underlying mechanism have shown that ER function declines during skeletal muscle aging, leading to the accumulation of unfolded or misfolded proteins [11], thereby inducing ER stress. In addition, a high level of mitochondrial ROS can also induce ER stress [66], and the skeletal muscle aging process can produce a large amount of ROS, thereby further promoting ER stress.…”
Section: Er Stress Levels Increases In Aging Skeletal Musclementioning
confidence: 99%
“…These data indicate an increase in ER stress levels in senile skeletal muscle. Studies on the underlying mechanism have shown that ER function declines during skeletal muscle aging, leading to the accumulation of unfolded or misfolded proteins [11], thereby inducing ER stress. In addition, a high level of mitochondrial ROS can also induce ER stress [66], and the skeletal muscle aging process can produce a large amount of ROS, thereby further promoting ER stress.…”
Section: Er Stress Levels Increases In Aging Skeletal Musclementioning
confidence: 99%
“…These studies have helped to characterize the physiological adaptations of healthy human muscle to different types of exercise (Rockl et al, 2007; Trappe et al, 2016). Most of these studies focused on the acute and immediate effects of short bouts of high intensity exercise in either human or mice/rat models (Guelfi et al, 2006; Egan and Zierath, 2013; Petriz et al, 2017), as well as long-term effects of exercise (Crane et al, 2013; Mosole et al, 2014; Belaya et al, 2018). However, very little research has focused on assessing the association of daily physical activity with the muscle proteome in healthy community-dwelling individuals.…”
Section: Introductionmentioning
confidence: 99%
“…oxidative stress, due to excessive reactive oxygen species (roS) production and impaired antioxidant defense mechanisms, induces a range of pathologies that are believed to be important contributors to the cardiovascular aging process (2,5). recently, Belaya et al (6) reported that long-term wheel running can protect against age-related cellular stress. The endoplasmic reticulum (er) is a specialized organelle where the folding and post-translational maturation of almost all membrane proteins, and most secreted proteins, occur (7).…”
Section: Introductionmentioning
confidence: 99%